Are the effects induced by increased temperature enhanced in Mytilus galloprovincialis submitted to air exposure? - Andrade, Madalena (2020)
Intertidal mussel species are frequently exposed to changes of environmental parameters related to tidal regimes that include a multitude of stressors that they must avoid or tolerate by developing adaptive strategies. In particular, besides air exposure during low tides, intertidal mussels are also subjected to warming and, consequently, to higher risk of desiccation. However, scarce information is available regarding the responses of mussels to tidal regimes, particularly in the presence of other stressors such as increased temperature. Investigating the impacts of such combination of conditions will allow to understand the possible impacts that both factors interaction may generate to these intertidal organisms. To this end, the present study evaluated the impacts of different temperatures (18 ºC and 21 ºC) on Mytilus galloprovincialis when continuously submersed or exposed to a tidal regime for 14 days. Results showed that in mussels exposed to increased temperature under submersion conditions, the stress induced was enough to activate mussels’ antioxidant defenses (namely glutathione peroxidase, GPx), preventing oxidative damage (lipid peroxidation, LPO; protein carbonylation, PC). In mussels exposed to tides at control temperature, metabolic capacity increased (electron transport system activity, ETS), and GPx was induced, despite resulting in increased LPO levels. Moreover, the combination of tides and temperature increase led to a significant decrease of lipid (LIP) content, activation of antioxidant defenses (superoxide dismutase, SOD; GPx) and increase of oxidized glutathione (GSSG), despite these mechanisms were not sufficient to prevent increased cellular damage. Therefore, the combination of increased temperature and air exposure induced higher oxidative stress in mussels. These findings indicate that increasing global warming could be more impacting to intertidal organisms compared to organisms continuously submersed. Furthermore, our results indicate that air exposure can act as a confounding factor when assessing the impacts of different stressors in organisms living in coastal systems